Ligand-induced activation of ERK1/2 signaling by constitutively active Gs-coupled 5-HT receptors - Liu Ping; Yin Yu-ling; Wang Ting; Hou Li; Wang Xiao-xi; Wang Man; Zhao Guan-guan; Shi Yi; Xu H. Eric; Jiang Yi (Acta Pharmacologica Sinica, 2019)
5-HT4R, 5-HT6R, and 5-HT7A,/SUB.R are three constitutively active Gs-coupled 5-HT receptors that have key roles in brain development, learning, memory, cognition, and other physiological processes in the central nervous system. In addition to Gs signaling cascade mediated by these three 5-HT receptors, the ERK1/2 signaling which is dependent on cyclic adenosine monophosphate (cAMP) production and protein kinase A (PKA) activation downstream of Gs signaling has also been widely studied. In this study, we investigated these two signaling pathways originating from the three Gs-coupled 5-HT receptors in AD293 cells. We found that the phosphorylation and activation of ERK1/2 are ligand-induced, in contrast to the constitutively active Gs signaling. This indicates that Gs signaling alone is not sufﬁcient for ERK1/2 activation in these three 5-HT receptors. In addition to Gs, we found that β-arrestin and Fyn are essential for the activation of ERK1/2. Together, these results put forth a novel mechanism for ERK1/2 activation involving the cooperative action of Gs, β-arrestin, and Fyn.